Observations of Aleutian Cackling Geese Branta hutchinsii leucopareia breeding on Buldir Island, Alaska: forty-seven years after discovery of a remnant population - Cocke, Josh; Alton, Steven K.; Black, Jeffrey M. (Wildfowl, 2016)
The once endangered Aleutian Cackling Goose Branta hutchinsii leucopareia sub-species has recovered to over 100,000 birds. In 2009, we revisited the largest known breeding colony on Buldir Island, Alaska, USA where the birds’ breeding biology was first studied during 1974–1977, when the population was only 1,700 individuals. We compared the density and distribution of nests, nesting chronology, clutch size, hatching success, and adult mass and size recorded in 2009 with the earlier data, finding: 1) increased nest densities, 2) expansion of nesting habitat into formerly unoccupied habitat strata, 3) smaller average clutch size, and 4) reduced post-breeding mass of females. Further studies are required to determine inter-annual variation in these variables and how breeding rates on Buldir Island compare with those on recently colonised, neighbouring sites within the Aleutian island chain.